Digitalization Strategy for Tailoring UMKM Branding in Mainan Village Banyuasin - Callistasari, Nidia Putri; Jannah, Raudatul; Aldi, Muhammad Rahmad; Alie, Juhaini; Munandar, Aris; Ghina, Aliah (Golden Ratio of Data in Summary, 2025)
This Community Service Program (KKN) was conducted in Mainan Village, Sembawa District, Banyuasin Regency, with a focus on branding digitalization strategies for local sewing MSMEs. The home-based sewing business targeted by the program is owned by Mrs. Sandiya, who previously lacked a business identity, such as a brand name, logo, banner, or attractive product packaging. The methods used included surveys and interviews, planning, implementation, and evaluation. The implementation stages included creating the business name "Sandiya Fashion", designing a logo, banner, packaging stickers, and creating social media accounts (Facebook) to expand marketing reach. The results of the mentoring showed increased brand awareness, ease of consumer recognition, and location of the business, and increased product visual appeal. This branding digitalization is expected to strengthen the business identity, expand the market, and encourage MSME sales growth in the technology era.